2019
DOI: 10.1111/ger.12430
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic determinants of edentulism in the elderly population: A systematic review and meta‐analysis

Abstract: Objective To provide a systematic review on the demographic and socioeconomic factors associated with edentulism among older persons. Background Edentulism (complete loss of the natural teeth) is one of the main problems affecting the oral health of the elderly individuals. Many unfavourable socioeconomic factors are considered important predictors of edentulism. Materials and methods This review was performed according to the preferred reporting items for systematic reviews and meta‐analyses (PRISMA). The sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
2
38
1
8
Order By: Relevance
“…Our findings are consistent with those of previous studies to have identified age and socioeconomic conditions as risk factors for tooth loss [11,12,28]. Aging populations have accumulated oral and non-communicable health conditions, and so remain susceptible to ongoing tooth loss.…”
Section: Plos Onesupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with those of previous studies to have identified age and socioeconomic conditions as risk factors for tooth loss [11,12,28]. Aging populations have accumulated oral and non-communicable health conditions, and so remain susceptible to ongoing tooth loss.…”
Section: Plos Onesupporting
confidence: 93%
“…Depending on its severity, it can significantly impact the ability to chew, speak, socialize, and overall general health [2,3,23]. While previous research has identified the determinants of tooth loss, most of this literature examined only edentulism and did not examine incremental tooth loss, which is a far more prevalent oral state [11]. Moreover, those studies were mostly based on cross-sectional data or examined a few variables using classical statistical modeling rather than predictive modeling [11,12,24].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Secondary analysis of nationwide oral health surveys in different countries reported the influence of poor individual socioeconomic characteristics, such as family income, occupational history and educational level, on tooth loss among elders and adults [5][6][7][8]. These findings are in accordance with a recent systematic that concluded that lower levels of education and poor income were meaningful factors associated with edentulism among elderly people [9].…”
Section: Introductionsupporting
confidence: 74%